Cardiac Involvement by Human Herpesvirus 8-Positive Diffuse Large B-Cell Lymphoma: An Unusual Presentation in a Patient with Human Immunodeficiency Virus - Elena M. Fenu; Michael W. Beaty; Tiffany E. O’Neill; Stacey S. O’Neill (Case Reports in Pathology)
Human immunodeficiency virus (HIV) infection predisposes patients to the development of lymphomas, both due to immune suppression and coinfection with viruses with oncogenic potential. Coinfection with human herpesvirus 8 (HHV8) in particular has been associated with the development of aggressive lymphomas, including primary effusion lymphoma and diffuse large B-cell lymphoma (DLBCL). Herein, we report an unusual case of HHV8-positive DLBCL with extensive cardiac involvement which was diagnosed at autopsy in a patient with long-standing untreated HIV infection.